2014
DOI: 10.1166/jnn.2014.8893
|View full text |Cite
|
Sign up to set email alerts
|

CO<SUB>2</SUB> Adsorption by Functionalized Nanoporous Materials: A Review

Abstract: This review highlights the recent advances in the development of functionalized nanoporous adsorbents for CO2 capture. Three main classes of materials are taken into account: zeolites, mesoporous silicates, and metal organic frameworks (MOFs). Proper modification of the cation content of zeolites, as well as the introduction of functional groups such as amine groups into ordered mesoporous silicates and MOFs, greatly enhance the CO2 adsorptive properties of these substrates. Specifically, cation-exchanged zeol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 0 publications
1
64
0
Order By: Relevance
“…On the other hand, activated carbon materials are usually adversely compared in terms of CO2 adsorption capacity and/or selectivity. Nevertheless, it has been proven that adsorption capacity and selectivity toward CO2 are strongly dependent on the porous structure and chemical surface of the adsorbent (Ruthven, 1984;Marsh and Rodríguez-Reinoso, 2006;Shafeeyan et al, 2010;Gargiulo et al, 2014). Specifically, it has been reported that at low CO2 partial pressures and room temperature, CO2 adsorption capacity is intrinsically related to micropores, although some discrepancies can be found in the literature.…”
mentioning
confidence: 99%
“…On the other hand, activated carbon materials are usually adversely compared in terms of CO2 adsorption capacity and/or selectivity. Nevertheless, it has been proven that adsorption capacity and selectivity toward CO2 are strongly dependent on the porous structure and chemical surface of the adsorbent (Ruthven, 1984;Marsh and Rodríguez-Reinoso, 2006;Shafeeyan et al, 2010;Gargiulo et al, 2014). Specifically, it has been reported that at low CO2 partial pressures and room temperature, CO2 adsorption capacity is intrinsically related to micropores, although some discrepancies can be found in the literature.…”
mentioning
confidence: 99%
“…Other possible applications could include heavy ion removal or an 17 environmental absorbent. [75,81,82] Perhaps the most interesting potential use of the films is in drug 18 delivery. It has already been shown how small amounts of hydrocarbons or alcohols can be incorporated into 19 micelles within the polymer-surfactant films.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we synthesized a hierarchical zeolite X with mesoporosity (Meso-13X) and attempted to make use of the mesoporosity to incorporate increased and better dispersed amine species inside its pore structure. Polyethylenimine (PEI) was chosen as the amine source, which was found to greatly enhance CO 2 capture when supported on mesoporous silica [18][19][20][21][22][23]. The effectiveness of PEImodified Meso-13X (Meso-13X-PEI) as a CO 2 adsorbent was tested in terms of its adsorption capacity, selectivity and stability.…”
Section: Introductionmentioning
confidence: 99%